1993
DOI: 10.3109/02713689309001827
|View full text |Cite
|
Sign up to set email alerts
|

The effect of caffeine on the accommodative response/accommodative stimulus function and on the response AC/A ratio

Abstract: Using a phoro-accommodometer, accommodation and convergence responses were measured for 17 experimental subjects before and after they ingested 200 mg caffeine. For 16 control subjects accommodation and convergence responses were determined at two test sessions separated by 45 min. For the experimental group, the accommodative response/accommodative stimulus (Ar/As) slope increased 0.05 D/D after ingestion of caffeine, and the response AC/A ratio decreased 3.05 delta/D. The y-intercept of the convergence respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The results of this study are in agreement with findings of earlier studies by other researchers suggesting changes of accommodative functions after caffeine consumption. [15][16][17] Kirshner and Schmid 15 investigated the extent to which the eye is able to relax accommodation through a +4.00 D lens after consumption of 150 mg caffeine in 11 subjects. The conclusion was that caffeine increased the tonicity of the ciliary muscles by about half of a diopter, hence resulting in the rejection of reading plus lens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study are in agreement with findings of earlier studies by other researchers suggesting changes of accommodative functions after caffeine consumption. [15][16][17] Kirshner and Schmid 15 investigated the extent to which the eye is able to relax accommodation through a +4.00 D lens after consumption of 150 mg caffeine in 11 subjects. The conclusion was that caffeine increased the tonicity of the ciliary muscles by about half of a diopter, hence resulting in the rejection of reading plus lens.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion was that caffeine increased the tonicity of the ciliary muscles by about half of a diopter, hence resulting in the rejection of reading plus lens. In addition, Zhai et al 16 studied changes in accommodative response at varied accommodative stimuli levels in 17 subjects before and after consumption of caffeine. They reported that caffeine increased the accommodative response only when the accommodative stimulus (object vergence) was not o5.00 D. We measured amplitude of accommodation of younger subjects with greater accommodation ability, hence all our subjects had a sustained blur at a distance of o20 cm (5.00 D).…”
Section: Discussionmentioning
confidence: 99%
“…The dissociation of these 2 functions is the basis of orthoptic treatment for certain types of accommodative esotropia. 14,23 Studies have also shown that the AC/A ratio is changed through surgery, 24,25 drugs, 14,26 and orthoptic treatment. 14,27 In Kushner's 8 study, two-thirds of patients with a high AC/A ratio who were treated with minus lenses showed ''normalization'' of their AC/A ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Particular attention has been given to the amplitude of accommodation and pupil size following the consumption of caffeine, with many studies reporting resultant increases in both the amplitude of accommodation 14,20 and pupil dilation. 14,21 The increase in the amplitude of accommodation is as a result of caffeine binding to the adenosine receptors.…”
Section: Introductionmentioning
confidence: 99%